Health and healthcare equity within the Canadian cancer care sector: a rapid scoping review - Leah K. Lambert; Tara C. Horrill; Scott M. Beck; Amber Bourgeois; Annette J. Browne; Shannon Cheng; A. Fuchsia Howard; Jagbir Kaur; Michael McKenzie; Kelli I. Stajduhar; Sally Thorne (BMC, 2023)
Abstract Background Despite a publicly-funded healthcare system, alarming cancer-related health and healthcare inequities persist in Canada. However, it remains unclear how equity is being understood and taken up within the Canadian cancer context. Our objective was to identify how health and healthcare equity are being discussed as goals or aims within the cancer care sector in Canada. Methods A rapid scoping review was conducted; five biomedical databases, 30 multidisciplinary websites, and Google were searched. We included English-language documents published between 2008 and 2021 that discussed health or healthcare equity in the Canadian cancer context. Results Of 3860 identified documents, 83 were included for full-text analysis. The prevalence of published and grey equity-oriented literature has increased over time (2008-2014 [n = 20]; 2015-2021 [n = 62]). Only 25% of documents (n = 21) included a definition of health equity. Concepts such as inequity, inequality and disparity were frequently used interchangeably, resulting in conceptual muddling. Only 43% of documents (n = 36) included an explicit health equity goal. Although a suite of actions were described across the cancer control continuum to address equity goals, most were framed as recommendations rather than direct interventions. Conclusion Health and healthcare equity is a growing priority in the cancer care sector; however, conceptual clarity is needed to guide the development of robust equity goals, and the development of sustainable, measurable actions that redress inequities across the cancer control continuum. If we are to advance health and healthcare equity in the cancer care sector, a coordinated and integrated approach will be required to enact transformative and meaningful change.